Unintended pregnancy in the amazon basin of Ecuador: a multilevel analysis - San Sebastian Miguel; Goicolea Isabel (BMC, 2010)
Abstract Background It has been estimated that each year 80 million women in the world experience an unintended pregnancy. In Ecuador, recent research has revealed that 36.3% of total births are unintended; the research also details significant geographical, ethnic and socioeconomic variations. These studies focused on individual risk factors and were based on large national surveys where local samples, particularly from rural remote areas, were small. The purpose of this study was to investigate the influence of contextual and individual factors on unintended pregnancies in the Amazon Basin of Ecuador. Methods Women aged 15-44 were selected through an ongoing community-based cross-sectional survey conducted in the Orellana province between May and December 2006. Data were fitted using multilevel logistic regression, adjusting for both individual-level and community-level factors as fixed effects and allowing for heterogeneity between communities. Results The overall prevalence of unintended pregnancy was 62.7%. Two-thirds (73.7%) of indigenous women reported having had at least one unintended pregnancy. Being young, single, and indigenous were significant risk factors for unintended pregnancy, alongside having low access to education and having more than two children. No relationship was found between socioeconomic status and the use of contraceptives. All the variation between communities was explained by individual-level factors. Conclusions This study showed the significance of individual factors in increasing the risk of unintended pregnancy, while the role of community factors was found to be negligible. In order for all women to be able to realize their right to reproductive autonomy, there needs to be a diverse range of solutions, with particular attention paid to cultural issues.